Application of a small AUV for mapping water column properties in the Baltic Sea - Taavi Liblik; Fred Buschmann (Frontiers in Marine Science, 2026)
The Baltic Sea observing system combines ship-based, autonomous, and remote-sensing components, yet major observational gaps persist in the shallow and dynamic coastal zone. Here, we present the first evaluation of a micro-autonomous underwater vehicle (micro-AUV) for high-resolution mapping of the Baltic Sea water column and assess its potential integration into regional coastal observing systems. Eleven missions were conducted in 2025 across three contrasting environments—the shallow estuarine Bay of Matsalu, the Suur Strait, and the coastal slope of the Baltic Proper—covering depths from 1 to over 100 m. The micro-AUV operated reliably under diverse hydrographic conditions, capturing fine-scale frontal, submesoscale, and benthic-layer structures, as well as a dual upwelling cell. Comparisons with reference profiles confirmed the high accuracy of temperature and salinity measurements, and strong correlations for chlorophyll-a fluorescence and turbidity. The vehicle’s endurance (up to 40 km or ~7 h at 1.5 m s −1 ) enables efficient mesoscale surveys, while its maneuverability allows operation in very shallow or complex coastal areas where gliders and floats cannot be used. The results demonstrate that micro-AUVs can fill a critical observational gap between ship-based surveys, gliders, FerryBoxes, and coastal stations by extending coastal observations offshore and resolving vertical structures inaccessible to remote sensing. Despite limitations in endurance and communication range, micro-AUVs represent a promising, cost-efficient addition to integrated coastal observing systems, supporting targeted process studies and rapid-response missions in dynamic environments such as the Baltic Sea.

A case study on microlitter and chemical contaminants: Assessing biological effects in the southern coast of the Gulf of Finland (Baltic sea) using the mussel Mytilus trossulus as a bioindicator - Ivan Kuprijanov; Natalja Buhhalko; Ulrika Eriksson; Viktor Sjöberg; Anna Rotander; Natalja Kolesova; Maarja Lipp; Fred Buschmann; Arslan Hashmi; Taavi Liblik; Kari K. Lehtonen (Marine Environmental Research, 2024)

High-resolution characterization of the development and decay of seasonal hypoxia in the Gulf of Riga, Baltic Sea - Taavi Liblik; Stella-Theresa Stoicescu; Fred Buschmann; Madis-Jaak Lilover; Urmas Lips (Frontiers in Marine Science, 2023)
The Gulf of Riga is a shallow basin in the eastern Baltic Sea connected to the Central Baltic Sea via shallow straits. Seasonal oxygen depletion occurs in the deep layer of the gulf. We conducted hourly measurements of dissolved oxygen, temperature, and salinity in the deep layer (50 m) of the gulf and observed the full cycle of development and relaxation of hypoxia in 2021. Hypoxia (<2.9 mg l -1 ) first occurred on 27 June and was observed for 71 days until its complete decay on 22 October. Average oxygen decline of 0.10 mg l -1 d -1 from saturation in mid-April until mid-July and 0.04 mg l -1 d -1 onwards until the end of August were observed. This seasonal pattern was superimposed by short-term variability in time scales from hours to days and was probably caused by inertial oscillations, (sub)mesoscale processes, deep layer currents, and pycnocline movements. Ventilation events with a relatively low impact and duration of up to ten days occurred in the deep layer due to the inflows of the saltier water from the Central Baltic. The inflowed water originated from the upper layer in winter and the thermocline in summer and was almost saturated in oxygen. Mostly mixing with existing oxygen-depleted water in the Gulf of Riga, but also local consumption declined the oxygen levels in the inflow water before it arrived at the observing station. Monthly standard deviations in oxygen varied from 0.3 to 2.8 mg l -1 and illustrated the added value of Eulerian measurements to complement the conventional monitoring.